Peningkatan Pemahaman Konsep Diri Anak Melalui Kegiatan Mengenal Anggota Tubuh dan Panca Indra - Saflitha, Widya; Zahriani Jf, Nurul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to improve early childhood children’s self-concept understanding through sensory recognition activities at RA Maghfirah. Self-concept is an important foundation for a child’s social-emotional development and can be fostered through activities related to the self, one of which is the activity of getting to know the sense organs. The study used a quantitative approach with a pre-experimental method of one group pretest–posttest design. The subjects of the study were 42 children of group B in RA Maghfirah. The instruments used were observation sheets and questionnaires. The results of the study showed that there was a significant improvement in the understanding of the child's self-concept after conducting the activity of recognizing the taste buds. The results of the data analysis showed that the child’s mean self-concept understanding score increased from 58.4 at the pretest to 84.2 at the posttest. These findings suggest that taste bud recognition activities are effective in improving early childhood self-concept understanding.